2016
DOI: 10.1111/jopr.12457
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Study of Factors Influencing the Performance of Digital Intraoral Impressions Operating on Active Wavefront Sampling Technology with Multiple Implants in the Edentulous Maxilla

Abstract: The TrueDef scanner provides measurements within clinically accepted limits. Yet scanbody visibility, observer experience, and scan length remain relevant factors affecting accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
148
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(161 citation statements)
references
References 27 publications
6
148
3
Order By: Relevance
“…Geometrical features on the scan bodies supply information about the implant orientation, angulation, and 3D spatial position within the dental arch . Digital implant scans can be performed directly following a digital workflow using intraoral scan bodies (ISBs) attached to the implants and an intraoral scanner (IOS) to capture the topography of the ISBs and the surrounding oral structures . Digital implant scanning techniques using direct digital workflow have been popular in recent years parallel with the development of various intraoral scanners (IOSs) and their reported advantages .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometrical features on the scan bodies supply information about the implant orientation, angulation, and 3D spatial position within the dental arch . Digital implant scans can be performed directly following a digital workflow using intraoral scan bodies (ISBs) attached to the implants and an intraoral scanner (IOS) to capture the topography of the ISBs and the surrounding oral structures . Digital implant scanning techniques using direct digital workflow have been popular in recent years parallel with the development of various intraoral scanners (IOSs) and their reported advantages .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the accuracy of intraoral digital implant scan is affected by several factors; the IOS system, software program associated with the digital scan system, different scan bodies, experience of the operator, angulation and position of the implant(s), and quadrant . In the literature, few studies have investigated the accuracy of ISBs that represents the 3D spatial position of implants …”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study with a six‐implant edentulous maxilla scenario and True Definition scanner reported that it provides clinically acceptable results, but there was no conventional control group as well (Gimenez‐Gonzalez et al. ). To the authors’ knowledge, there are no data on the accuracy of full‐arch digital implant impressions made with the Omnicam and True Definition scanners compared with conventional impressions.…”
mentioning
confidence: 99%
“…Hence, the decision was made to fabricate working casts from conventional impressions and to subsequently digitize them with a high precision laboratory scanner (Activity 880 scanner). Comparative studies are currently emerging showing that full‐arch digital implant impressions with different IOS such as TRIOS, Omnicam and True Definition scanner have the same or even better accuracy as the conventional ones …”
Section: Discussionmentioning
confidence: 99%